Elites' perceptions of women's representation in the Omani media - Al-Wahaibi, Sumaiya (Frontiers in Sociology, 2025)
IntroductionThis study investigates how Omani elites perceive women's representation in national media and how structural, cultural, and political forces shape gender narratives in the Sultanate. It explores how women's visibility is instrumentalized to project modernization while maintaining patriarchal authority, situating the Omani case within broader Gulf Cooperation Council (GCC) media-gender dynamics.MethodsThe research draws on 38 semi-structured elite interviews conducted between 2021 and 2025 with parliamentarians, journalists, academics, activists, and government officials. Interviews were analyzed using reflexive thematic analysis within the frameworks of state feminism, neopatriarchy, and symbolic annihilation, complemented by media observation and document analysis to triangulate findings.ResultsFindings reveal that women's visibility in Omani media is predominantly symbolic and event-based, emphasizing ceremonial achievements and depoliticized empowerment. Elites describe a system where modernization coexists with patriarchal control, producing what can be termed “modernization without liberation.” Media governance and restrictive laws-such as those protecting the “majesty of the state,” limit editorial independence and suppress rights-based gender discourse. Women are often silenced or stereotyped, with their lived realities of discrimination and inequality omitted from mainstream narratives.Discussion and conclusionsThe study argues that women's representation in Omani media functions as a technology of legitimacy within an authoritarian developmental model that merges inclusionary rhetoric with moral governance. Moving beyond symbolic visibility requires reforms that strengthen media autonomy, institutionalize women's participation in decision-making, and expand digital pluralism. Such measures could transform Omani media from a vehicle of state image management into a platform for genuine dialogue, justice, and equality, contributing to wider debates on gender, media, and state-society relations in the GCC.